(untitled) (KULT_online, 2012)
Peace research often refers to Immanuel Kant, who saw a causal connection between the internal and political constitution of states and their foreign policy. Therefore, republican states are supposed to have less interest in foreign-policy conflicts than others. To fathom this theorem, a meeting was held at the European Academy in Berlin in 2009 by the ’working group on historical peace research’. The result of this conference was a volume which critically examines the interpretation ’democracy=peace’ from different disciplinal perspectives, describes its genesis, and compares theory and practice. The book gives a general idea of basic concepts of peace research; nevertheless, it is ultimately unable to answer the question whether the aforesaid theory can claim validity.